ANALYSIS OF TAX COMPLIANCE OF MSME OWNERS AFTER THE TAX HARMONISATION LAW - Aprilian, Rahil Imainul; S, M Afdal (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Tax is one of the largest sources of state revenue. Tax compliance can increase government revenue and improve the stability of a country’s economy. As one of the driving tools of the country’s economy, MSMEs are also closely related to taxes. To increase tax awareness among MSME owners, the government has provided a small portion of the income tax rate to MSME owners, equivalent to 0.5% of the company’s gross turnover (sales) based on the HPP Law if it exceeds Rp.500,000,000.00. This qualitative study aims to analyze the understanding of MSME tax actors in the South Bangka region by understanding the current tax rates and office of MSME actors. The survey shows that MSME actors’ understanding of the reduction in income tax rates and tax administration is still low. Lower income tax rates and poor tax administration performance lead to low tax compliance among MSME actors.